Aloperine Ameliorates Acetaminophen-Induced Acute Liver Injury through HMGB1/TLR4/NF-κB and NLRP3/Inflammasome Pathway - Hui Chen; Shu Wang; Qiuyue Chen; Wen Yu; Hao Nie; Lian Liu; Bing Zheng; Quan Gong (Hindawi Limited, 2024)
Purpose. Aloperine (ALO), an alkaloid isolated from Sophora alopecuroides L., possesses multiple pharmacological activities and holds a promise potential for the treatment of various clinical conditions, including skin hypersensitivity, cancer, and inflammatory disorders. The purpose of this study was to investigate the role of ALO in acetaminophen (N-acetyl-para-aminophenol (APAP))-induced acute liver injury and its underlying mechanisms. Materials and Methods. An animal model of acute liver injury was induced by intraperitoneal injection of APAP (150 mg/kg). Prior to APAP injection, ALO (40 mg/kg) was administered daily for 7 consecutive days. Serum alanine aminotransferase, aspartate aminotransferase, and lactate dehydrogenase levels were then measured using an automated chemical analyzer. Histopathological changes were evaluated using hematoxylin and eosin staining. Oxidative stress levels were measured by detecting superoxide dismutase (SOD), glutathione (GSH), and malondialdehyde (MDA). Pro-inflammatory cytokines were detected in serum and liver tissues using ELISA and quantitative real-time polymerase chain reaction (q-PCR). The expression of members of the HMGB1/TLR4/NF-κB signaling pathway and NLRP3 inflammasome were determined by Western blot and/or q-PCR. In addition, the expression and location of NLRP3, cleaved caspase-1, high-mobility group box 1 (HMGB1), and phosphorylated p65 (p-p65) were detected by immunofluorescence. Results. Pretreatment with ALO significantly protected mice from APAP-induced acute liver injury, with decreased MDA content, and significantly increased GSH and SOD activities. Furthermore, ALO pretreatment reduced the release of pro-inflammatory cytokines (IL-1β and TNF-α) and decreased the expression of caspase-1, cleaved caspase-1, and NLRP3. In addition, ALO pretreatment also inhibited the activation of the HMGB1/TLR4/NF-κB signaling pathway. Conclusion. Taken together, ALO can ameliorate APAP-induced acute liver injury by inhibiting oxidative stress, inflammation by inhibiting the HMGB1/TLR4/NF-κB, and NLRP3/inflammasome pathway.